Communication best practices at Dell, General Electric, Microsoft, and Monsanto - Cushman, Donald P. (SUNY series in human communication processes., 2003)
"Through case studies of communication best practices at Dell, General Electric, Microsoft, and Monsanto, this book provides specific and powerful theories for leadership, marketing, and stockholder communication. Best practice limitations are also revealed in the cases of IBM, the Bumper Works, and Asea Brown and Boveri, where organizational learning, a firm's timeline, and corporate culture made implementation difficult. Taken collectively, these case studies suggest several ways in which benchmarking can become an important research methodology and theorist tool for understanding excellence in organizational practice."--Jacket